2021
DOI: 10.1101/2021.08.17.456682
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single cell based high-throughput Ig and TCR repertoire sequencing analysis in rhesus macaques

Abstract: Recent advancements in microfluidics and high-throughput sequencing technologies have enabled recovery of paired heavy- and light- chains of immunoglobulins (Ig) and VDJ- and VJ- chains of T cell receptors (TCR) from thousands of single cells simultaneously in humans and mice. Despite rhesus macaques being one of the most well-studied model organisms for the human adaptive immune response, high-throughput single cell immune repertoire sequencing assays are not yet available due to the complexity of these polyc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…8 using rigorous scRNAseq and functional analysis identified a subset of PBMC cells that expressed both Ig and T cell receptor transcripts. Furthermore, searching the raw antibody data (http:// ireceptor.irmacs.sfu.ca/) of healthy human antibody repertoires of conventional B cells from the study by Briney et al,3 we found the unique CDR3 sequence (CARQEDTAMVYYFDYW) of the B cell receptor x-clonotype (Figure 1E, Reference [2].…”
mentioning
confidence: 99%
“…8 using rigorous scRNAseq and functional analysis identified a subset of PBMC cells that expressed both Ig and T cell receptor transcripts. Furthermore, searching the raw antibody data (http:// ireceptor.irmacs.sfu.ca/) of healthy human antibody repertoires of conventional B cells from the study by Briney et al,3 we found the unique CDR3 sequence (CARQEDTAMVYYFDYW) of the B cell receptor x-clonotype (Figure 1E, Reference [2].…”
mentioning
confidence: 99%
“…Our analysis of these primers shows them to be suitable for enrichment of TRA and TRB genes from rhesus macaques, and therefore this set of primers can be used for both species of macaques [25]. Similarly, nested primers for rhesus TCR enrichment using the 10X Genomics platform can also be used for cynomolgus macaques as the regions to which they anneal are 100% conserved [35,36].…”
Section: Discussionmentioning
confidence: 97%